2015
DOI: 10.1245/s10434-015-4454-y
|View full text |Cite
|
Sign up to set email alerts
|

Distant Metastases in Patients with Carcinoma of the Major Salivary Glands

Abstract: Background This study aimed to show the incidence of distant metastases (DM) in salivary gland cancer as well as the types of histology most commonly associated with it and to identify factors predictive of DM. Methods The study identified 301 patients who underwent surgery for cancer of the major salivary glands at Memorial Sloan-Kettering Cancer center between 1985 and 2009. Clinical, tumor, and treatment characteristics were recorded. Tumors were categorized as low-, intermediate-, and high-risk pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
61
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 16 publications
13
61
3
1
Order By: Relevance
“…In the review by Bradley, it was reported that the rate of distant failure in salivary gland cancer ranges between 20% and 40% with a higher rate in high‐grade tumors. Other retrospective studies on salivary gland cancer also reported a high rate of distant metastasis in high‐grade tumors . Ali et al showed a 5‐year distant failure rate of 18.9% in all patients with salivary gland cancer and of 47.3% in patients with high‐grade tumors.…”
Section: Discussionmentioning
confidence: 94%
“…In the review by Bradley, it was reported that the rate of distant failure in salivary gland cancer ranges between 20% and 40% with a higher rate in high‐grade tumors. Other retrospective studies on salivary gland cancer also reported a high rate of distant metastasis in high‐grade tumors . Ali et al showed a 5‐year distant failure rate of 18.9% in all patients with salivary gland cancer and of 47.3% in patients with high‐grade tumors.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study found distant metastases in only seven of 454 (1.5%) patients at initial staging, but the number increased to 95 (20.0%) during the median follow‐up of 100 months (Nam et al., ). Another study suggested that distant metastases were present in 57 of 266 (18.9%) patients with SGC during a median follow‐up of 43 months (Ali et al., ). The most common site for distant metastasis was the lung, with the proportion ranging from 50% to 78%, while metastases in multiple organs were also very common (Ali et al., ; Nam et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies demonstrated risk factors influencing SGC survival, with tumor size, histological grade, N classification, and distant metastases reported as being associated with cancer‐specific survival and OS outcomes (Ali et al., , ; Bussu et al., ; Roh et al., , ). The metastatic potential of SGC differs substantially according to different sites, pathology, and histological grade (Ali et al., ; Cheung, Franzmann, Sola, Pincus, & Koniaris, ; Ko et al., ; Nam et al., ). Of more than 24 different SGC pathologies, adenoid cystic carcinoma and salivary duct carcinoma have high rates of distant metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other head and neck malignancies in which the common sites of recurrence are the primary site and/or the regional lymph node, salivary gland cancer usually recurs at the primary and/or distant sites . The most common distant metastatic site is the lungs, followed by the bones, liver, or central nervous system . Some patients undergo multiple surgeries, but most usually progress to a point where they are not amenable to surgery .…”
Section: Introductionmentioning
confidence: 99%